A comparison of methods for measuring thermal insulation of military clothing. (October 2021) - Švecová, Jana; Strohmandl, Jan; Fišer, Jan; Toma, Róbert; Hajna, Petr; Havelka, Antonín
This study presents methods for measuring thermal insulation of military clothing assemblies used in various climatic regions of the world, with the exception of polar regions. With the use of FOX 314 and thermal manikin, the thermal insulation of the fabrics (military materials) was ascertained at simulating real climatic conditions of cold, arid, temperate and tropical zones according to European standard EN 60721-2-1: 2014. The aim of this study was to compare the values of thermal insulation of the duty of military clothing ascertained by two methods and to evaluate the reliability of methods and instruments used. The measured results show that the measurement methods used are different in terms of method and measurement conditions, the results of the thermal insulation and the resulting choice of military clothing in the type of climate. The functionality and suitability of the use of military clothing sets were verified in real climatic conditions, provided that the optimal thermal comfort of the wearer was achieved.